DIPG-59. LOW GRADE DIFFUSE INTRINSIC PONTINE GLIOMA? A SINGLE INSTITUTION EXPERIENCE. Issue 2 (22nd June 2018) - Shatara, Margaret; Sood, Sandeep; Poulik, Janet M; Altinok, Deniz; Miller, Steven; Liu, Xuehui; Wang, Zhihong
Abstract: Diffuse Intrinsic Pontine Glioma (DIPG) is an extensively invasive tumor of brainstem. Tumor biopsy was rarely performed until recently, because of the possible complications associated with the procedure, therefore, the data on the DIPG histology is relatively limited. We identified 29 consecutive cases of DIPG diagnosed from 2002 to 2017 at Children's Hospital of Michigan, and tumor biopsy was performed in 22 cases. The histology was consistent with low grade glioma (LGG) in 4 of the 22 cases (18%). We retrospectively reviewed these 4 cases, including the histology, MRI findings, H3 mutation and BRAF alteration status, treatment and survival. There was one Grade I astrocytoma, one Grade I ganglioglioma, and two grade II astrocytomas. Radiologically, 3 were consistent with typical DIPG, one with atypical DIPG. The testing for H3 mutation and BRAF alteration was performed in two recent cases. One case had H3F3A K27 mutation, but no BRAF alteration was identified in either case. All patients received involved-field external beam radiation as part of their initial treatment. Three patients succumbed to their disease with overall survival of 9–17 months, and one patient is alive with no clinical or radiological sign of disease at 6 months following diagnosis. In summary, histology was consistent with LGG in 4 out of 22(18%) of our biopsied DIPG series. One patient with ganglioglioma was found to have histone H3 mutation, a rare finding in LGG but common in midline high grade glioma, who progressed at 11 months, and died at 17 months following initial diagnosis.